PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL MITSUBISHI PADA PT. SARDANA INDAH BERLIAN MOTOR MEDAN - Andre Riady; David Tandreas; Andre Fernandes Riady; Hardy Wijaya; Charles Harry Faska Gultom; Melkyory Andronicus (JEBIM Prima, 2021)
This research was conducted in PT Sardana Indah Berlian Motor Medan. The purpose of this study was to examine and analyze the effect of product quality, service quality and price on purchasing decisions for Mitsubishi cars in PT Sardana Indah Berlian Motor Medan. The decision to buy Mitsubishi cars has decreased. This research method uses quantitative methods. The population in this study amounted to 1376 customers and the sample amounted to 93 customers. The sampling technique of this research is simple random sampling. Testing the hypothesis partially obtained the value of tcount -0.710 <1.987 and the significance obtained is 0.480 > 0.05, meaning that H0 is accepted and Ha is rejected, namely partially Product Quality has no significant effect on purchasing decisions for Mitsubishi cars in PT. Sardana Indah Berlian Motor Medan. Testing the hypothesis partially obtained the value of tcount -0.062 < 1.987 and the significance obtained is 0.951 > 0.05, meaning that H0 is accepted and Ha is rejected, namely partially Service Quality has no significant effect on purchasing decisions for Mitsubishi cars in PT. Sardana Indah Berlian Motor Medan. Testing the hypothesis partially obtained the value of tcount -0.91 <1.987 and the significance obtained is 0.928> 0.05, meaning that H0 is accepted and Ha is rejected that is partially the price has no significant effect on purchasing decisions for Mitsubishi cars in PT. Sardana Indah Berlian Motor Medan. The results of the simultaneous test are Fcount = 0.168 < Ftable 2.71 and the significance probability is 0.918 > 0.05. It can be concluded that H0 is accepted and Ha is rejected, namely simultaneously Product Quality, Service Quality and Price have no significant effect on the Mitsubishi Car Purchase Decision variable in PT. Sardana Indah Berlian Motor Medan.